2000
DOI: 10.1001/jama.283.13.1715
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vignettes, Standardized Patients, and Chart Abstraction

Abstract: Our data indicate that quality of health care can be measured in an outpatient setting by using clinical vignettes. Vignettes appear to be a valid and comprehensive method that directly focuses on the process of care provided in actual clinical practice. Vignettes show promise as an inexpensive case-mix adjusted method for measuring the quality of care provided by a group of physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
344
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,050 publications
(358 citation statements)
references
References 58 publications
6
344
1
7
Order By: Relevance
“…Direct observation of the performance of providers can be completed through the use of standardized patients 31 or video recording of clinicians interacting with patients. 32 Similarly, assessments of competency, including questionnaires about knowledge, can be completed (e.g., those done as part of the requirements for certification by the American Board of Internal Medicine or through completion of clinical vignettes).…”
Section: At the Care-provider Levelmentioning
confidence: 99%
“…Direct observation of the performance of providers can be completed through the use of standardized patients 31 or video recording of clinicians interacting with patients. 32 Similarly, assessments of competency, including questionnaires about knowledge, can be completed (e.g., those done as part of the requirements for certification by the American Board of Internal Medicine or through completion of clinical vignettes).…”
Section: At the Care-provider Levelmentioning
confidence: 99%
“…Another concern might be the use of vignettes to search for evidence of stereotyping in decision-making, although several studies have shown vignettes to be accurate in reflecting actual clinical practice. [39][40][41][42][43] The survey response rate among students at participating schools (40.2 %) is low enough that some might question the validity of the sample. Although our data show relatively few differences among survey respondents and the larger population of senior medical students as depicted by the AAMC survey, suggesting sample validity, it is possible that non-participants and students from non-participating schools may demonstrate different decision-making tendencies than those reflected in these data.…”
Section: Discussionmentioning
confidence: 99%
“…Although often criticized because they do not reflect actual practice which may influence results and conclusions of studies, well designed vignette studies can be practical, offer flexibility, avoid ethical and observational issues and be generalizable to real world settings (Evans et al, 2015;Peabody, Luck, Glassman, Dresselhaus & Lee, 2000;Rutten, Harting, Rutten, Bekkering & Kremers, 2006). Clinical vignettes are an inexpensive option to control multiple variables, collect information simultaneously from multiple sources, and isolate clinical decision making.…”
Section: Overview Of Problemmentioning
confidence: 99%
“…For instance, real patients may make measurement by direct observation difficult to apply, especially in larger samples, can be expensive and time-consuming, and is potentially subject to a Hawthorne effect (Rutten et al, 2006). Use of real patients may result in insufficient case mix (Peabody et al, 2000) which may inadvertently introduce sampling bias, especially as it relates to MDT. The Derangement syndrome is the most common classification in the spine (78%, May, 2006) and in the extremity (37%, May & Rosedale, 2012).…”
Section: Clinical Vignettesmentioning
confidence: 99%
See 1 more Smart Citation